MORPHOLOGICAL CHARACTERISTICS AND PLEASANT RELATIONSHIP BETWEEN CROSSING OF BLACK RICE ACCESION WITH INPARA 5 THAT CONTAINING SUB-1 GENES - Gladysha, Utary; Halimi, E.S; Hasmeda, Mery; Sarimana, Upit (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2021)
In South Sumatra the cultivation of black rice is uncommon. This is because of the lack of available land for planting which can be used to grow local black rice. Since more farmers dominate the white rice or brown rice cultivation. One effort that can be made to increase the area of local black rice planting areas is to use South Sumatra's vast swampy land. Related to the previous study, this research will be carried out by testing the growth of F1 seeds crossed by accession to high productivity local black rice and nutrition with marinated resistant Inpara 5 varieties. In quantitative parameters, the maximum average value of it was shown at the age of 12 MST plants that IM.6 plants at 145.08 as the highest average value of the crossing results. IM.6 was the highest median value with 144.5. The maximum standard deviation value was 5.06 for IT.11 plants, and the minimum value being 141.4 for IM.6 forms and 150.0.6 for IM.6 plants. The qualitative parameters consist of plant shape, stem color, leaf color, and flag leaf are seen when the plant is 6 MST or in the vegetative phase. Done by describing plants from 5 sample plants per randomly selected population. From the result of this research, there is no significant differential between accession and parental.